The Third Space: Shared Understanding between Aboriginal and Non-Aboriginal People - Todd, Helen Joan (Curtin University, 2018)
A concept of Baldja Leadership is presented following a study of enablers and inhibitors of shared understanding between Aboriginal and Non Aboriginal people working in the Western Australian civil construction industry. Leadership traits perceived by members of both cultures as creating positive and negative regard for their leaders were identified. This constructivist, interpretivist investigation recommends actions to achieve a 'third space' of understanding that will help to retain Aboriginal people in organizations